Trends in overweight and obesity in soldiers entering the US Army, 1989‐2012. (22nd January 2015) - Hruby, Adela; Hill, Owen T.; Bulathsinhala, Lakmini; McKinnon, Craig J.; Montain, Scott J.; Young, Andrew J.; Smith, Tracey J.
<x xml:space="preserve">Abstract</x> Objective The US Army recruits new soldiers from an increasingly obese civilian population. The change in weight status at entry into the Army between 1989 and 2012 and the demographic characteristics associated with overweight/obesity at entry were examined. Methods 1, 741, 070 unique individuals with complete sex, age, and anthropometric information contributed data to linear and logistic regressions examining time trends and associations between demographic characteristics and overweight/obesity. Results The prevalence of overweight (body mass index 25‐<30 kg/m2) generally increased, from 25.8% (1989) to 37.2% (2012), peaking at 37.9% (2011). The prevalence of obesity (body mass index ≥30 kg/m2) also increased from 5.6% (1989) to 8.0% (2012), peaking at 12.3% (2009); 2005‐2009 annual prevalence exceeded 10%. The most consistent demographic characteristics predicting overweight/obesity were male sex, older age, Hispanic or Asian/Pacific Island race/ethnicity, and being married. There were no distinct geographic trends. Conclusions The US Army is not immune to the US obesity epidemic. Demographic characteristics associated with being overweight or obese should be considered when developing military‐sponsored weight management programs for new soldiers.